Research on Hoisting Method of Reinforcement Cage for Underground Continuous Wall. Issue 1 (March 2020) - Liu, Mingqi; Dai, Bihui; Liu, Dewen
Abstract: The hoisting method of reinforcement cage in a diaphragm wall project is studied. Through certain graphic display, the process of hoisting the reinforced cage was described. In this paper, we propose a specific method of hoisting a 880mm thick of reinforcement cage, and the entire specific process and technology of lifting it is also offered. During the hoisting procedure and the lifting transformation process, reinforcement cage hoisting is an important part of construction, and this article has certain reference value to the construction process.